CD68, CD163, and matrix metalloproteinase 9 (MMP-9) co-localization in breast tumor microenvironment predicts survival differently in ER-positive and -negative cancers - Pelekanou, Vasiliki (Breast Cancer Res, 2018)
BACKGROUND: The role of tumor-associated macrophages (TAMs) in the cancer immune landscape and their potential as treatment targets or modulators of response to treatment are gaining increasing interest. TAMs display high molecular and functional complexity. Therefore their objective assessment as breast cancer biomarkers is critical. The aims of this study were to objectively determine the in situ expression and significance of TAM biomarkers (CD68, CD163, and MMP-9) in breast cancer and to identify subclasses of patients who could benefit from TAM-targeting therapies. METHODS: We measured CD68, CD163, and MMP-9 protein expression in formalin-fixed paraffin-embedded tissues of breast carcinomas represented in tissue microarray format using multiplexed quantitative immunofluorescence (QIF) in two independent Yale cohorts: cohort A—n = 398, estrogen receptor–positive (ER(+)) and ER(−) cases—and the triple-negative breast cancer (TNBC)-only cohort B (n = 160). Associations between macrophage markers, ER status, and survival were assessed. Protein expression measured by QIF was compared with mRNA expression data from the METABRIC study. RESULTS: All three macrophage markers were co-expressed, displaying higher expression in ER(−) cancers. High pan-macrophage marker CD68 correlated with poorer overall survival (OS) only in ER(−) cases of cohort A (P = 0.02). High expression of CD163 protein in TAMs was associated with improved OS in ER(−) cases (cohort A, P = 0.03 and TNBC cohort B, P = 0.04, respectively) but not in ER(+) cancers. MMP-9 protein was not individually associated with OS. High expression of MMP-9 in the CD68(+)/CD163(+) TAMs was associated with worse OS in ER(+) tumors (P <0.001) but not in ER(−) cancers. In the METABRIC dataset, mRNA levels followed the co-expression pattern observed in QIF but did not always show the same trend regarding OS. CONCLUSIONS: Macrophage activity markers correlate with survival differently in ER(+) and ER(−) cancers. The association between high co-expression and co-localization of MMP-9/CD163/CD68 and poor survival in ER(+) cancers suggests that these cancers may be candidates for macrophage-targeted therapies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13058-018-1076-x) contains supplementary material, which is available to authorized users.